2020
DOI: 10.3892/ol.2020.12067
|View full text |Cite
|
Sign up to set email alerts
|

A prognosis‑predictive nomogram of ovarian cancer with two immune‑related genes: <em>CDC20B</em> and <em>PNPLA5</em>

Abstract: Ovarian carcinoma (OV) is one of the most lethal gynecological malignancies globally, and the overall 5-year survival rate of OV was 47% in 2018 according to American data. To increase the survival rate of patients with OV, many researchers have sought to identify biomarkers that act as both prognosis-predictive markers and therapy targets. However, most of these have not been suitable for clinical application. The present study aimed at constructing a predictive prognostic nomogram of OV using the genes ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Han Lin et al found that CDC20B is one of the prognostic genes in ovarian cancer patients through sequencing and data analysis. The gene is overexpressed in ovarian cancer tissue (Lin et al, 2020). Longfei Yang et al found that CDC20B is one of the therapeutic targets of the novel anti-tumour peptide SA12, which can provide targeted therapy for breast cancer (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Han Lin et al found that CDC20B is one of the prognostic genes in ovarian cancer patients through sequencing and data analysis. The gene is overexpressed in ovarian cancer tissue (Lin et al, 2020). Longfei Yang et al found that CDC20B is one of the therapeutic targets of the novel anti-tumour peptide SA12, which can provide targeted therapy for breast cancer (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The included studies 11,35–47,54–61 used models built based on the TCGA cohort and involved all types of breast cancer. The final results showed that our signature and three other prognostic signatures, namely, a 21 immune‐related gene signature, 35 17 immune‐related gene signature 36 and 17 TF‐related gene signature 37 performed better than the other hallmark signatures in the prediction of OS in patients with OV 11,35,38–47,54–61 . Additionally, Yu et al has constructed a five GRG signature (ANGPTL4, PYGB, ISG20, SEH1L and IRS2) for patients with OV 62 .…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the predictive ability of our signature, a comparison was performed among several significant molecular signatures that were employed for predicting OS in patients with OV. The included studies 11 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 used models built based on the TCGA cohort and involved all types of breast cancer. The final results showed that our signature and three other prognostic signatures, namely, a 21 immune‐related gene signature, 35 17 immune‐related gene signature 36 and 17 TF‐related gene signature 37 performed better than the other hallmark signatures in the prediction of OS in patients with OV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the advances in the field of OC treatment and implementation of standard therapy, the prognosis for OC patients is poor, and the five-year survival rate is only 47% [ 2 ]. For comparison, the five-year survival rate for cervical cancer totals 66% and for uterine cancer 81% [ 3 ].…”
Section: Ovarian Cancer—a Global Problemmentioning
confidence: 99%